A NEED ANALYSIS OF PROFESSIONAL DEVELOPMENT PROGRAM FOR ELEMENTARY SCHOOL ENGLISH TEACHERS THROUGH SELF-ASSESSMENT (IAIN Syekh Nurjati Cirebon, 2022)
Many homeroom teachers in elementary schools are demanded to teach English. Meanwhile, they lack knowledge of English teaching to young learners. They need a professional development program that can assist them to improve their teaching competence. Therefore, this research is aimed at analyzing the needs of teacher professional development programs by assessing English elementary school teachers through self-assessment. It is a descriptive quantitative research that involves 30 elementary teachers who have English teaching experience. A survey was conducted to find out teachers’ weaknesses that could portray teachers’ teaching needs. The result shows that most teachers assumed their speaking and listening skills were below average levels. In terms of pedagogical competence, they assessed themselves as insufficient in determining English teaching methods, giving appropriate assessments, applying various and fun English learning, teaching speaking & teaching listening. Thus, a teacher professional development program should be able to facilitate teachers to improve these professional and pedagogical aspects.